PENGEMBANGAN KOMIK DIGITAL BERBASIS KEARIFAN LOKAL PADA MATERI BANGUN DATAR KELAS III SD - Nasah Lubis, Lady; Dalimawaty Kadir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop digital comic media comic based on local wisdom using plane materials elementary level students grade 3. The development research used ADDIE (Analysis Design Development Implementation Evaluation). The instrument used to collect the data was a questionnaire given to several expert reviewers. They are digital comic media expert validation, material expert validation, language expert validation, teacher response and student responses. The validation score obtained from material expert reviewers was 93, from digital comic media experts 83, language experts (linguist) 84, teacher’s response 87 and students responses 92. The average score obtained from all experts in the evaluation phase was 87.8Of all scores obtained from all validation, it can be said that digital comic media witch based on the local wisdom was very appropriate. Thus, for these who would like to develop plane materials it is very good to use digital comic media which based on the local wisdom.The implementation result that the elementary students grade 3 got 82 with the local wisdom approach. there is an increase in learning outcomes, where previously the average score for students on plane material was 65.6.